2009
DOI: 10.1177/0022034509354843
|View full text |Cite
|
Sign up to set email alerts
|

NOD1 and NOD2 Mediate Sensing of Periodontal Pathogens

Abstract: In bacterial infection, Nucleotide-binding Oligomerization Domain (NOD) 1 and NOD2 induce innate immune responses by recognizing fragments of the bacterial component peptidoglycan (PGN). To determine the roles of these receptors in detection of periodontal pathogens, we stimulated human embryonic kidney cells expressing NOD1 or NOD2 with heat-killed Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum or their soluble PGNs (sPGNs). All bacteria and their sPGNs could stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 32 publications
3
46
0
1
Order By: Relevance
“…Upon incubation of the HEK293T cells with A. actinomycetemcomitans OMVs, we observed a strong activation of the cytoplasmic PRRs NOD1 and NOD2, supporting the presence of NOD1-and NOD2-active peptidoglycan in the vesicles. This is consistent with earlier in vitro studies using the HEK293T cell reporter assay, revealing that soluble A. actinomycetemcomitans PGN and heat-killed cells of this species act as potent inducers of both NOD1 and NOD2 (42). Conversely, another recent report using the same cell-based reporter assay suggested that the tested A. actinomycetemcomitans strain mainly triggered NOD1 (44).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Upon incubation of the HEK293T cells with A. actinomycetemcomitans OMVs, we observed a strong activation of the cytoplasmic PRRs NOD1 and NOD2, supporting the presence of NOD1-and NOD2-active peptidoglycan in the vesicles. This is consistent with earlier in vitro studies using the HEK293T cell reporter assay, revealing that soluble A. actinomycetemcomitans PGN and heat-killed cells of this species act as potent inducers of both NOD1 and NOD2 (42). Conversely, another recent report using the same cell-based reporter assay suggested that the tested A. actinomycetemcomitans strain mainly triggered NOD1 (44).…”
Section: Discussionsupporting
confidence: 91%
“…It is conceivable that such a functional role of vesicles may be evident mainly in oral species possessing peptidoglycan with high NOD1-stimulatory activity, such as A. actinomycetemcomitans and the closely related mouse commensal NI1060. In contrast to these Pasteurellaceae species, Bacteroidetes organisms, including P. gingivalis, possess peptidoglycan exhibiting low levels of NOD1-stimulatory activity (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOD1 recognizes peptidoglycan, a component of the bacterial cell wall, whereas NOD2 recognizes muramyl dipeptide, a peptidoglycan constituent of both Gram-positive and Gram-negative bacteria (Figure 2). 133 A different set of NLRs, including Ipaf and Naip, are activated through bacterial flagellin. NLRP3 (cryopyrin) is activated through a variety of molecules, including bacterial RNA, pore-forming toxins and endogenous ligands, including uric acid crystals and ATP.…”
Section: Nox Innate Immunity and Bacterial Infectionsmentioning
confidence: 99%
“…Others studies have shown that supragingival and subgingival biofilms differently regulate the gene expressions of NLRP3 and AIM2 inflammasomes in human gingival fibroblasts (Bostanci et al, 2011), and the downregulation of NLRP3 and IL-1β expression is partly induced by P. gingivalis present in subgingival biofilms (Belibasakis et al, 2013). Although NOD1 and NOD2 are involved in the recognition of periodontal pathogens and in the immune responses modulation (Okugawa, 2010), the effect of its activation in osteoclast is still unknown. To investigate the role of the NOD2 receptor in osteoclastogenesis and bone resorption, we used an experimental periodontitis model with NOD2-deficient mice.…”
mentioning
confidence: 99%